2012
DOI: 10.3945/jn.111.140103
|View full text |Cite
|
Sign up to set email alerts
|

Administration of High Doses of Copper to Capuchin Monkeys Does Not Cause Liver Damage but Induces Transcriptional Activation of Hepatic Proliferative Responses

Abstract: Liver cells respond to copper loading upregulating protective mechanisms. However, to date, except for liver content, there are no good indicators that identify individuals with excess liver copper. We hypothesized that administering high doses of copper to young (5.5 mg Cu · kg⁻¹ . d⁻¹) and adult (7.5 mg Cu · kg⁻¹ . d⁻¹) capuchin monkeys would induce detectable liver damage. Study groups included adult monkeys (2 females, 2 males) 3-3.5 y old at enrollment treated with copper for 36 mo (ACu); age-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Thirdly, compared with WGs, there were no significant differences in T-AOC levels when the copper concentration was ≤0.99 mg/L ( p > 0.05). In the end, excessive copper concentrations (1.33 and 2.00 mg/L) significantly reduced T-AOC levels under all doses, which was consistent with the report by Araya et al (2012) that long-term high copper loading would lead to a reduction in relevant antioxidant capacity indicators [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…Thirdly, compared with WGs, there were no significant differences in T-AOC levels when the copper concentration was ≤0.99 mg/L ( p > 0.05). In the end, excessive copper concentrations (1.33 and 2.00 mg/L) significantly reduced T-AOC levels under all doses, which was consistent with the report by Araya et al (2012) that long-term high copper loading would lead to a reduction in relevant antioxidant capacity indicators [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…Analysis of hepatic content of copper provided very high values, suggesting copper as the causative agent in this patient. In animals, however, overdosed copper administration caused no liver injury as assessed by light microscopy [119][120][121] or only minimal, partially dose dependent changes such as small vacuoles of hepatocytes, hepatocyte swelling, inflammatory cells, or sinusoidal congestion [118]. Electron microscopy data on the liver of the patient exposed to high amounts of copper were not available [116,117] but have been reported in animal studies as irregularly shaped nuclei, abundant mitochondria, and displayed cristae, and hepatocytes with inclusion of secondary lysosomes [120].…”
Section: Coppermentioning
confidence: 95%
“…Wilson disease is a genetic disorder of the liver leading to hepatic copper accumulation [3,4], and the earlier termed Indian childhood diseases were in fact cases of Wilson disease rather than caused by exposure to exogenous copper in drinking water or milk as previously assumed by error [114]. Experimental studies in animals showed mostly unchanged or in rare cases slightly increased serum ALT and AST activities after application of high copper amounts [118][119][120].…”
Section: Coppermentioning
confidence: 99%
“…High copper has an opposite effect on protein localization, but not under all circumstances. The decreased levels of mCTR1 at the PM were observed in the liver tissue with a prolonged (20 weeks) intracellular accumulation of copper (Ralle et al, 2010), whereas high dietary copper did not seem to have such an effect (Araya et al, 2012). Altogether, these observations raise an interesting possibility that under physiologically relevant conditions the distribution of CTR1 between the intracellular and PM pools is controlled by the metabolic demands of a cell (i.e.…”
Section: Copper Auto Regulates Its Cytoplasmic Levels By Modulating Tmentioning
confidence: 99%